Design and Fabrication of Oil Palm Loose Fruit Collector - Johnny, Calvin Dio; Saleh, Aslinda (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The loose fruit collection procedure gets more attention than the other processes since it offers the highest rate of oil extraction. The technique for collecting the loose fruits usually uses a hand and collects into the bucket but the workers need to bend over to collect loose fruit on the ground which can cause back pain. This project proposes a loose fruit collector with more ergonomic lightweight and easier to use. It begins with the analysis of the research and the survey regarding the problems faced by the workers and the specific design requirements of the respondents. To develop the collector’s concept, the eight phases of George E. Dieter’s engineering design process were followed, benchmarking existing market items and patents. SolidWorks software was used to identify and model the optimal concept and enable thorough engineering investigation, including static analysis. After extensive engineering calculations and simulations in SolidWorks, the final product design has overall dimensions of 500 x 432 x 825 mm for the basket and 320 x 96 x 1260 mm for the rake. The entire weight of the product, including fasteners, is 4 kg. It is anticipated that these creative collectors would greatly increase the effectiveness and simplicity of upholding Malaysia’s ergonomic work culture